Green and blue infrastructure: means of reducing surface temperatures in the urban environment - Sedláček, Jan (Jihočeská univerzita, 2021)
Climate change may accelerate the Urban Heat Island (UHI) effect with many consequences for the well-being of human populations in cities. Green and blue infrastructures (GBI) are presented as a way to mitigate the UHI effect. In our study, the influence of GBI (primarily less studied types) on surface temperature (ST) was tested using a thermal camera. Various types of GBI (e. g. tree shade and lawn) and their combination were compared.
Green and blue infrastructure: means of reducing surface temperatures in the urban environment
Keywords: surface temperature; urban climate; microclimate; urban heat island; UHI; green infrastructure; blue infrastructure; greenery; vegetation; green roof; green wall fountain; well-being; tree shade; climate change; thermal amplitudes; surface temperature; urban climate; microclimate; urban heat island; UHI; green infrastructure; blue infrastructure; greenery; vegetation; green roof; green wall fountain; well-being; tree shade; climate change; thermal amplitudes